2011
DOI: 10.4028/www.scientific.net/amr.328-330.1326
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of a Modified Sponge Iron for Removing Dissolved Oxygen

Abstract: In order to improve the performance of sponge iron for removing dissolved oxygen, sponge iron was originally modified by chemical replacement copper plating and the optimum modifying condition was obtained by orthogonal experiments. The effect of each modifying condition on the dissolved oxygen (DO) level in the outlet treated by modified sponge iron was investigated. The operating condition of packed bed was also investigated. The results showed that the performance of modified sponge iron for removing DO was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Therefore, it is necessary to modify sponge iron aimed at promoting the deoxygenization performance. It is reported that modifying with chemical replacement copper plating is able to promote the deoxygenization performance sharply [3]. The aim of the present work was to investigate the deoxygenization mechanism with the aid of kinetics and characterized analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to modify sponge iron aimed at promoting the deoxygenization performance. It is reported that modifying with chemical replacement copper plating is able to promote the deoxygenization performance sharply [3]. The aim of the present work was to investigate the deoxygenization mechanism with the aid of kinetics and characterized analysis.…”
Section: Introductionmentioning
confidence: 99%